Prevalence the Premenstrual Syndrome (PMS) in Pakistani Women - Shagufta Perveen, Naila Mairaj, Muniba Maqbool, Ahmad Bilal, Sara Munir, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: to determine the prevalence the premenstrual syndrome (PMS) in Pakistani women of child bearing age and the frequency of practices regarding premenstrual syndrome in Pakistani women of child bearing age. Methodology: this cross sectional study included 250 cases, during 2013. A history was taken regarding their menstrual cycle and an interview was carried out. The answers to the questions on the interview were recorded on previously designed performa. The presence or absence of premenstrual syndrome was noted and the patients were also asked about details of symptoms of premenstrual syndrome and treatment related to it. Results: During the study period,250 women were included in study. Out of 250 women, 174(69.6%) had one or more symptoms of premenstrual syndrome (p<0.0001) 80% had awareness of symptoms regarding premenstrual syndrome and treatment relate to it.(P<0.05). Conclusion: The prevalence of premenstrual syndrome among women under study was high and clinically significant.(p<0.0001). Keywords: Premenstrual syndrome, PMS, PMDD, Dysmorphic Disorder, DSM criteria IV, menstrual cycle